STRATEGI PENGEMBANGAN AGROWISATA EDUKASI PERTANIAN DI DESA BESUR KECAMATAN SEKARAN KABUPATEN LAMONGAN - Aiman, Muhammad Yassar; Nugroho, Sigit Dwi; Amir, Indra Tjahaja (Berkala Ilmiah AGRIDEVINA, 2021)
This research aims to identify internal and external factors in the development of agricultural education agrotourism in Besur Village and analyze the strategies that have been implemented and formulate alternative strategies for agricultural education agrotourism in Besur Village. The data used in this study are primary data and secondary data. Primary data is data taken directly from the research location of the agro-tourism area for agricultural education through direct observation at the site, and interviews. 46 respondents were selected including 10 agro-tourism structuralists and 36 agro-tourism visitors. Secondary data is data obtained through agencies related to this research. The analytical method used is SWOT analysis. Based on the results of the study, it was concluded that the dominant strength factor was cheap ticket prices. The dominant weakness factor is post-harvest processing that is less than optimal. The dominant opportunity factor is agro-tourism as a place for learning outside the classroom so that it is not saturated in the classroom. The dominant threat factor is the change of seasons which reduces the aesthetic elements of the tourist attraction. The strategy that must be carried out is aggressive (Growth oriented strategy). Strategies that need to be optimized include, maximizing tourism with the concept of rural nature and education, utilizing low ticket prices as alternative tourism, optimizing tourism services with local institutions and communities, utilizing information technology to promote educational tourism as a place to learn outside the classroom. DOI : https://doi.org/10.33005/adv.v10i1.2620